Utilizing Game-Based American Simulation Pedagogy to Teach Norwegian Students American Studies - Erik Mustad; Maren Anderson Johnson; Sean Taylor (American Studies in Scandinavia)
In Scandinavian countries, the teaching of American studies has traditionally taken place within the discipline of English. In recent years, English has moved away from the predominantly Anglo-American approach to include perspectives from a wider range of English-speaking countries. American studies is devoted less class time than it used to get, and consequently, new methods of teaching and learning need to be adopted. This paper argues that the American immersion pedagogy Reacting to the Past (RTTP), an in-class game method that takes students to historical moments through characters acting out American historical twists, is an excellent high-impact teaching method. RTTP is a student-centered pedagogy that offers engagement and active learning of American history to Norwegian students. Through collected data from English students at the University of Agder, the paper aims to discuss how this methodology can enhance learning and integration of American studies.